Optical switch based on cascaded SOI nonlinear directional coupler - Tao, Qing; Luo, Fengguang; Cai, Dusi; Liang, Qianliang; Wan, Zhengwen; Song, Xinming; Liu, Xuechao (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
In this paper, we calculate three effective refractive indexes for cascaded silicon-on-insulator (SOI) nonlinear directional coupler. For each effective refractive index, the coupling length LC, core-to-distance-ratio K and switching threshold power Pi, m are calculated, respectively. However, there are some fabrication errors, which are ΔW, ΔH, ΔK in the height of Si layer and width of Si layer and error of core-to-distance-ratio. We have analyzed the influence of power transmission efficiency Ti, j and relative transmission efficiency error Δi, j caused by the change of ΔW, ΔH, ΔK. Furthermore, we find the tolerance range of ΔW, ΔH, ΔK for Ti, j and Δi, j in couplers a, b, c. The other four input pulses with different powers are switched to four different ports. Although output pulses show some little compression and loss, the value of η is very small and output pulse waveforms are not affected seriously. The basic switching function has been realized, so this design is proved to be effective.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 669-678
Keywords: optyka; silicon-on-insulator (SOI); vector finite element; discrete split-step multi-wavelet transfor-mation; coupled nonlinear Schrödinger equation (CNLSE)